Biomechanical and neuromuscular differences between professional and varsity football players during countermovement and approach jumps - Gabriela Garcia; Rafaela Bucheli; Jose Tomas Castillo; Julian Fernandez; Alejandra de la Torre; Andres Leon Fierro; Wendy Montiel; Paul G. Arauz (PLoS ONE, 2025)
This study aimed to compare lower-body kinematics, muscle activity, performance, and vertical ground reaction force (GRFz) metrics between professional and varsity Ecuadorian football players during countermovement jumps with arm swing (CMJ AS ) and approach jumps (AJ). These two jump types were selected because they closely reflect common football-specific movement patterns; CMJ AS simulates vertical jumps with arm drive, while AJ mimics explosive jumping after a run-up. Forty athletes (20 professional, 20 varsity; equally distributed by sex) were assessed using synchronized motion capture, force plates, and surface electromyography. Professional males demonstrated greater force production efficiency, defined here as the ability to generate higher concentric average GRFz, higher braking peak GRFz, shorter movement durations, and higher rates of force development in the unloading, yielding and braking phases, while achieving similar jump heights and modified reactive strength index (RSI mod) to varsity players during CMJ AS . However, they also experienced higher impact forces in the AJ. Among females, professionals outperformed varsity players in both jumps, achieving greater jump heights, higher RSI mod scores, and increased concentric average GRFz. They also exhibited higher landing impact forces, loading rates, and asymmetric vastus medialis mean activation during landing; patterns commonly associated with elevated injury risk. Across groups, joint range of motion (ROM) and muscle activation patterns varied by phase, with professionals generally showing more proximal muscle activation and neuromuscular control. Asymmetries in ROM and muscle activation were more pronounced among professional females, particularly during AJ, suggesting task-specific adaptations that may also influence injury susceptibility. These findings underscore the importance of a comprehensive biomechanical assessment to inform injury screening and targeted strategies for injury risk reduction in competitive football.